TOX3 deficiency mitigates hyperglycemia by suppressing hepatic gluconeogenesis through FoxO1 - Liu, Congcong; Zheng, Yuanwen; Hu, Shourui; Liang, Xiaofan; Li, Yuxuan; Yu, Zhiheng; Liu, Yue; Bian, Yuehong; Man, Yuanyuan; Zhao, Shigang; Liu, Xin; Liu, Hongbin; et al. (Metabolism, clinical and experimental, 2024)
Excessive hepatic glucose production is a hallmark that contributes to hyperglycemia in type 2 diabetes (T2D). The regulatory network governing this process remains incompletely understood. Here, we demonstrate that TOX3, a high-mobility group family member, acts as a major transcriptional driver for hepatic glucose production. Tox3-overexpressed and knockout mice were constructed to explore its metabolic functions. Transcriptomic and chromatin-immunoprecipitation sequencing (ChIP-seq) were used to identify downstream targets of TOX3. Both FoxO1 silencing and inhibitor approaches were used to assess the contribution of FoxO1. TOX3 expression levels were examined in the livers of mice and human subjects. Finally, Tox3 was genetically manipulated in diet-induced obese mice to evaluate its therapeutic potential. Hepatic Tox3 overexpression activates the gluconeogenic program, resulting in hyperglycemia and insulin resistance in mice. Hepatocyte-specific Tox3 knockout suppresses gluconeogenesis and improves insulin sensitivity. Mechanistically, integrated hepatic transcriptomic and ChIP-seq analyses identify FoxO1 as a direct target of TOX3. TOX3 stimulates FoxO1 transcription by directly binding to and activating its promoter, whereas FoxO1 silencing abrogates TOX3-induced dysglycemia in mice. In human subjects, hepatic TOX3 expression shows a significant positive correlation with blood glucose levels under normoglycemic conditions, yet is repressed by high glucose during T2D. Importantly, hepatic Tox3 deficiency markedly protects against and ameliorates the hyperglycemia and glucose intolerance in diet-induced diabetic mice. Our findings establish TOX3 as a driver for excessive gluconeogenesis through activating hepatic FoxO1 transcription. TOX3 could serve as a promising target for preventing and treating hyperglycemia in T2D. Schematic diagram of TOX3 induction of hepatic gluconeogenesis and hyperglycemia. TOX3 binds to the promoter of FoxO1 to activate its transcription, which in turn drives hepatic gluconeogenic program, thereby leading to glucose intolerance and insulin resistance. TOX3 deficiency could efficiently suppress hepatic gluconeogenesis and improve glucose homeostasis under diet-induced diabetes. [Display omitted] •TOX3 acts as a key transcriptional driver for hepatic gluconeogenesis and hyperglycemia.•Hepatic Tox3 knockout improves glucose homeostasis by suppressing gluconeogenesis and improving insulin sensitivity in mice.•TOX3 orchestrates hepatic transcriptional program by directly activating FoxO1 transcription.•TOX3 deficiency prevents and ameliorates hyperglycemia in diet-induced diabetic mice.